2018
DOI: 10.18517/ijaseit.8.5.4641
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gamma Radiation on Plant Morphological Characteristics of Zingiber officinale Roscoe

Abstract: Induced mutation through gamma irradiation can cause changes in chromosome and genome, which bring to successful variation in the morphology of plant. This study investigates the effect of gamma radiation on mutation frequency and plant morphology of Zingiber officinale Roscoe. The ginger rhizomes of Bentong and Tanjung Sepat cultivars were treated with gamma rays at six different dosages (5, 7, 9, 11, 13, and 15 Gray). The gamma ray was emitted from the Caesium-137 source at the rate of 4.31 Gy per minute at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…This suggests irradiated plants have better adaptability in high-temperature environments than control plants. Low-dose irradiation alters hormonal signals in plant cells or increases the number of anti-oxidative cells to cope with environmental stress [11]. Increased dose of irradiation linear with an increase in leaf area although not significant.…”
Section: Leaf Areamentioning
confidence: 88%
See 1 more Smart Citation
“…This suggests irradiated plants have better adaptability in high-temperature environments than control plants. Low-dose irradiation alters hormonal signals in plant cells or increases the number of anti-oxidative cells to cope with environmental stress [11]. Increased dose of irradiation linear with an increase in leaf area although not significant.…”
Section: Leaf Areamentioning
confidence: 88%
“…Low doses of gamma-ray irradiation can stimulate tissue meristem activity, triggering high plant growth, but high doses of irradiation can damage plant cells. Hydroxyl radicals are products produced by reactions between water and radiation that cause damage to chromosomes [11]. High doses of gamma-ray irradiated seeds can disrupt plant growth because hormone balance, protein synthesis, and enzyme activity are disrupted [12], such as reduced bioactive content of Giberelat Acid (GA) or inhibition of GA signaling [13].…”
Section: Table 1 Plant Height Of Echinacea Purpurea Plant At Various ...mentioning
confidence: 99%
“…Amasya; Surakshitha and Soorianathasundaram 22 in grapes cv. Red Globe and Muscat; Yadav 38 in Canscora decurrens Dalz; Al-Mousa et al 36 in grape cv. Black Matrouh.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were no significant differences in node number and internode distance between the control and low doses of γ irradiation, whereas high doses of γ irradiation resulted in dwarf plants with short internode distances. Additionally, Abdullah et al 36 reported that the variation in plant height in the mutants was caused by an alteration in the intermodal length. Growth internode decreases may be due to auxin disintegration, ineffective assimilation systems, or suppression of mitosis and chromosomal destruction, leading to secondary physiological and morphological effects.…”
Section: Discussionmentioning
confidence: 99%
“…A mutation breeding scheme is one of the tools to develop a new variety. Mutations cause changes in various characters, including morphology [5], physiology [6], and agronomy [7][8], resulting in mutants with new characters that are different from the original cultivars. Some of the changes are positive and useful in breeding programs, such as increased plant height and cane yield [9].…”
Section: Introductionmentioning
confidence: 99%